Managing renal injury in the elderly patient - Haase-Fielitz, Anja; Haase, Michael (Springer Berlin Heidelberg, 2014)
As the number of people aged 65 years and above rises, physicians are increasingly confronted by elderly patients with impaired renal function, altered drug metabolism and multiple comorbidities. This book examines in detail the nature of renal injury in the elderly and its optimal management. A wide range of key topics are covered, including end-stage renal disease, diabetic nephropathy, acute kidney injury, drug metabolism and renal toxicity, dialysis and its complications and the use of renal transplantation. In addition, the assessment of glomerular filtration rate in the elderly and the role of novel renal biomarkers are carefully examined. Quality of life issues, the significance of other age-related medical problems and end of life care are also discussed. This book will be of value not only to nephrologists but also to general practitioners, medical students, intensivists, cardiologists, pharmacologists and those working in related specialties.